Quantum Teleportation via Optical Communication Channels - Chai, Nong; Pao, Chai; Chai, Som (Journal of Tecnologia Quantica, 2024)
Quantum teleportation through optical communication channels is one of the promising technologies to create secure communication systems in the future. This study aims to evaluate the efficiency of quantum teleportation through various types of optical communication channels, such as standard optical fibers, low-loss optical fibers, and free photon-based communication lines. The research was conducted using a quantitative experimental method, measuring the success rate of teleportation based on channel length, channel type, and environmental disturbances. The results showed that low-loss optical fibers had the highest efficiency, with a success rate of 85% at distances of up to 50 km. The free photon-based path shows good performance at short distances, but decreases drastically at longer distances due to atmospheric disturbances. The study also found that photon loss and environmental disturbances are the main factors affecting entanglement stability, especially in channels more than 75 km long. The conclusion of this study confirms that low-loss optical fiber is the best choice to support quantum teleportation on a local to medium scale. The main challenges in the development of this technology are the reduction of photon loss and the management of environmental disturbances. Further research is needed to address these limitati